Desain Game Edukatif STEMphoria untuk Meningkatkan Kemampuan Berpikir Kritis - Rumodhon, Berliansyah; Fikriyati, Amiq; Pandiangan, Kawan (Jurnal Sains dan Teknologi (JSIT), 2026)
STEM learning at the school level and in pre-service teacher education still faces problems related to low student engagement and limited development of critical thinking skills, which are largely caused by the use of conventional and less contextual learning media. These conditions highlight the need for innovative learning media that integrate technology, meaningful learning experiences, and problem-solving challenges. This study aims to design and develop STEMphoria as a web-based educational game that supports STEM learning while fostering critical thinking skills among students and pre-service teachers. This research employed a Research and Development (R&D) method, consisting of needs analysis, game concept design, prototype development, and limited initial testing. Data were collected through observations, interviews, and user perception questionnaires, while the data analysis technique used was descriptive qualitative analysis to evaluate the feasibility of the product and users’ responses to the developed game. STEMphoria was designed using a game-based learning approach integrated with thematic narratives, progressive problem-solving challenges, and virtual experiment simulations to enhance users’ cognitive engagement. The results of the study indicate that the resulting product, in the form of the STEMphoria game design and prototype, is perceived as engaging and challenging, and is able to provide immediate feedback on players’ decisions. Preliminary trials suggest that STEMphoria has the potential to serve as a relevant and contextual alternative learning medium to support the development of critical thinking skills in STEM education. Further research is required to examine the effectiveness of STEMphoria more comprehensively in formal instructional settings.